Modelling the annual NHS costs and outcomes attributable to healthcare-associated infections in England - Julian F Guest; Dinah Gould; Tomas Keating; Neil Wigglesworth (BMJ Open)
Objectives To estimate the annual health economic impact of healthcare-associated infections (HCAIs) to the National Health Service (NHS) in England.Design A modelling study based on a combination of published data and clinical practice.Setting NHS hospitals in England.Primary and secondary outcome measures Annual number of HCAIs, additional NHS cost, number of occupied hospital bed days and number of days front-line healthcare professionals (HCPs) are absent from work.Results In 2016/2017, there were an estimated 653 000 HCAIs among the 13.8 million adult inpatients in NHS general and teaching hospitals in England, of which 22 800 patients died as a result of their infection. Additionally, there were an estimated 13 900 HCAIs among 810 000 front-line HCPs in the year. These infections were estimated to account for a total of 5.6 million occupied hospital bed days and 62 500 days of absenteeism among front-line HCPs. In 2016/2017, HCAIs were estimated to have cost the NHS an estimated £2.1 billion, of which 99.8% was attributable to patient management and 0.2% was the additional cost of replacing absent front-line HCPs with bank or agency staff for a period of time. When the framework of the model was expanded to include all NHS hospitals in England (by adding specialist hospitals), there were an estimated 834 000 HCAIs in 2016/2017 costing the NHS £2.7 billion, and accounting for 28 500 patient deaths, 7.1 million occupied hospital bed days (equivalent to 21% of the annual number of all bed days across all NHS hospitals in England) and 79 700 days of absenteeism among front-line HCPs.Conclusion This study should provide updated estimates with which to inform policy and budgetary decisions pertaining to preventing and managing these infections. Clinical and economic benefits could accrue from an increased awareness of the impact that HCAIs impose on patients, the NHS and society as a whole.